MIR503HG Loss Promotes Endothelial-to-Mesenchymal Transition in Vascular Disease. Issue 8 (11th March 2021) - Monteiro, João P.; Rodor, Julie; Caudrillier, Axelle; Scanlon, Jessica P.; Spiroski, Ana-Mishel; Dudnakova, Tatiana; Pflüger-Müller, Beatrice; Shmakova, Alena; von Kriegsheim, Alex; Deng, Lin; Taylor, Richard S.; Wilson-Kanamori, John R.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Endothelial-to-mesenchymal transition (EndMT) is a dynamic biological process involved in pathological vascular remodeling. However, the molecular mechanisms that govern this transition remain largely unknown, including the contribution of long noncoding RNAs (lncRNAs). Objectives: To investigate the role of lncRNAs in EndMT and their relevance to vascular remodeling. Methods and Results: To study EndMT in vitro, primary endothelial cells were treated with transforming growth factor-β2 and interleukin-1β. Single-cell and bulk RNA-seq (RNA-sequencing) were performed to investigate the transcriptional architecture of EndMT and identify regulated lncRNAs. The functional contribution of seven lncRNAs during EndMT was investigated based on a DsiRNA (dicer-substrate short interfering RNAs) screening assay. The loss of lncRNA MIR503HG was identified as a common signature across multiple human endothelial cell types undergoing EndMT in vitro. MIR503HG depletion induced a spontaneous EndMT phenotype, while its overexpression repressed hallmark EndMT changes, regulating 29% of its transcriptome signature. Importantly, the phenotypic changes induced by MIR503HG were independent of miR-424 and miR-503, which overlap the lncRNA locus. The pathological relevance of MIR503HG downregulation was confirmed in vivo using sugen/hypoxia–induced pulmonary hypertension in mice, as well as in human clinical samples, in lung sections and blood outgrowth endothelial cells from pulmonary arterial hypertension patients. Overexpression of human MIR503HG in sugen/hypoxia mice led to reduced mesenchymal marker expression, suggesting MIR503HG therapeutic potential. We also revealed that MIR503HG interacts with the PTBP1 (polypyrimidine tract binding protein 1) and regulates its protein level. PTBP1 regulation of EndMT markers suggests that the role of MIR503HG in EndMT might be mediated in part by PTBP1. Conclusions: This study reports a novel lncRNA transcriptional profile associated with EndMT and reveals the crucial role of the loss of MIR503HG in EndMT and its relevance to pulmonary hypertension.